2007
DOI: 10.1088/0004-6256/135/1/55
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Spectra of Centaurs and Kuiper Belt Objects

Abstract: We present here an extensive survey of near-infrared (NIR) spectra of Kuiper belt objects (KBOs) and Centaurs taken with the Keck I Telescope. We find that most spectra in our sample are well characterized by a combination of water ice and a featureless continuum. A comparative analysis reveals that the NIR spectral properties have little correlation to the visible colors or albedo, with the exception of the fragment KBOs produced from the giant impact on 2003 EL61. The results suggest that the surface composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 54 publications
(44 reference statements)
3
68
0
Order By: Relevance
“…4), as reported by previous authors . The depth of this band seems slightly different between the three different spectra even if the signal to noise ratio is more limited for the data of Barkume et al (2008) and Pinilla-Alonso et al (2007). The slope in the near infrared is similar in the three cases as well as the slope observed in the visible spectra.…”
Section: Overview Of the Spectral Behaviormentioning
confidence: 68%
See 1 more Smart Citation
“…4), as reported by previous authors . The depth of this band seems slightly different between the three different spectra even if the signal to noise ratio is more limited for the data of Barkume et al (2008) and Pinilla-Alonso et al (2007). The slope in the near infrared is similar in the three cases as well as the slope observed in the visible spectra.…”
Section: Overview Of the Spectral Behaviormentioning
confidence: 68%
“…We obtained near-infrared spectra for 12 Barkume et al 2008). Our spectrum shows the presence of crystalline water ice because of a strong absorption feature at 1.65 µm (see Fig.…”
Section: Overview Of the Spectral Behaviormentioning
confidence: 93%
“…4). Barkume et al [38] found a weak correlation between object size and the fraction of water ice detected on the surfaces of the KBOs in their sample indicating that larger objects generally show stronger water ice absorption features. However, no such correlation was found for the Centaurs [38].…”
Section: 32mentioning
confidence: 91%
“…To first order, the surfaces of small and midsized KBOs and centaurs can be described with a two-component model consisting of dark (likely carbon-rich) deposits and exposed crystalline water ice [7,38]. The spectra of these objects can be parameterized as a linear mixture between a featureless continuum component (with a variable slope) and crystalline water ice [7,38].…”
Section: Non Volatile-rich Objectsmentioning
confidence: 99%
See 1 more Smart Citation